2018
DOI: 10.1016/j.molmet.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids are important direct and indirect regulators of the secretion of appetite- and metabolism-regulating hormones from the gut and pancreas

Abstract: ObjectiveBile acids (BAs) facilitate fat absorption and may play a role in glucose and metabolism regulation, stimulating the secretion of gut hormones. The relative importance and mechanisms involved in BA-stimulated secretion of appetite and metabolism regulating hormones from the gut and pancreas is not well described and was the purpose of this study.MethodsThe effects of bile acids on the secretion of gut and pancreatic hormones was studied in rats and compared to the most well described nutritional secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 53 publications
3
142
0
2
Order By: Relevance
“…Thus, the aim of this study was to test whether the effects of SGLT2 on glucagon secretion demonstrated in vitro could be reproduced in a more physiological setting. As glucagon secretion is tightly regulated by blood glucose, which is lowered by SGLT2 inhibitors, we chose the isolated perfused rat pancreas as experimental model [6,7], where perfusate glucose is kept constant. We studied the effects of the SLGT2 inhibitor dapagliflozin, the SGLT1/2 inhibitor phloridzin and the metabolically inert SGLT-specific substrate methyl-α-D-glucopyranoside (α-MGP) on glucagon secretion in this model.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the aim of this study was to test whether the effects of SGLT2 on glucagon secretion demonstrated in vitro could be reproduced in a more physiological setting. As glucagon secretion is tightly regulated by blood glucose, which is lowered by SGLT2 inhibitors, we chose the isolated perfused rat pancreas as experimental model [6,7], where perfusate glucose is kept constant. We studied the effects of the SLGT2 inhibitor dapagliflozin, the SGLT1/2 inhibitor phloridzin and the metabolically inert SGLT-specific substrate methyl-α-D-glucopyranoside (α-MGP) on glucagon secretion in this model.…”
Section: Introductionmentioning
confidence: 99%
“…Application of 100 μmol/L TDCA, via the vasculature, in perfused rat small intestine, robustly increased GLP-1 release, whereas luminal application of TDCA at the same concentration was significantly less effective, 29 presumably because TDCA stimulates GLP-1 secretion by postabsorptive activation of basolateral located Taconic-G-proteincoupled receptors (TGR5). 30 Our results indicate that ABA is more LANCL2 has been identified as the mammalian receptor mediating the functional effects of ABA in mammals. 21,31,32 ABA, via LANCL2 binding, stimulates insulin release and insulin-independent glucose uptake in myocytes and adipocytes and induces brown fat activity.…”
Section: Aba Stimulates Glp-1 Secretion From the Proximal Small Intmentioning
confidence: 66%
“…Nevertheless, it should also be noted that ABA administration in the intestinal perfusion system gave similar results to taurodeoxycholate (TDCA). Application of 100 μmol/L TDCA, via the vasculature, in perfused rat small intestine, robustly increased GLP‐1 release, whereas luminal application of TDCA at the same concentration was significantly less effective, presumably because TDCA stimulates GLP‐1 secretion by post‐absorptive activation of basolateral located Taconic‐G‐protein‐coupled receptors (TGR5) . Our results indicate that ABA is more effective, at least in this experimental setting, when acting from the vascular side compared with the luminal side: however, a direct effect of luminal ABA, in vivo, on GLP‐1 release cannot be excluded.…”
Section: Discussionmentioning
confidence: 79%
“…Bile acids are ligands of the G‐protein‐coupled receptor Takeda G‐protein‐coupled receptor 5 (TGR5), and the nuclear receptor farnesoid X receptor (FXR), both of which are expressed in L‐cells. In preclinical models, activation of TGR5 by bile acids increases GLP‐1 secretion, whereas activation of FXR has been reported to result in both suppression and stimulation of GLP‐1 secretion. For example, FXR null mice have been observed to have better glucose control and enhanced GLP‐1 secretion in some studies, but impaired glucose tolerance in others .…”
Section: Gastrointestinal Effects Of Metformin: Role Of Gut Peptidesmentioning
confidence: 99%